Safety guidelines for youth agricultural work in the United States: A description of the development and updating process - Swenson, Andrea V. R.; Salzwedel, Marsha; Peltier, Cassandra; Lee, Barbara C. (Frontiers in Public Health, 2023)
To reduce the prevalence of youth injuries and fatalities in agricultural settings, safety professionals considered developing a guideline-focused intervention for how and when youth should conduct farm chores. In 1996, the process to create guidelines started, which then expanded to include professionals from the United States, Canada, and Mexico. This team used a consensus driven approach to develop the guidelines and launch the North American Guidelines for Children’s Agricultural Tasks. By 2015, research related to the published guidelines indicated a need to incorporate new empirical evidence and develop dissemination plans based on new technologies. The process for updating the guidelines was supported by a 16-person steering committee and used content experts and technical advisors. The process yielded updated and new guidelines, now called Agricultural Youth Work Guidelines. This report responds to request for further details on the development and update of the guidelines and describes the genesis of the guidelines as an intervention, the process for creating guidelines, recognition of the need to update guidelines based on research, and the process for updating guidelines to assist in others engaged in similar types of interventions.